Analisis Motif Tren PayLater pada Kalangan Anak Muda di Kota Solo dalam Perspektif Syariah - Yafenia Putri Tirta Biru; Mufti Arief Arfiansyah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The Indonesian government declares an increase in NPF of BNPL distribution to young people. This study aims to determine the effect of life needs, lifestyle, peer attachment, and sharia financial literacy on paylater usage decisions among young people in Solo. This study employs quantitative methodology, employing path analysis with SPSS version 27 as the data analysis tool. The research population consisted of Solo-domiciled Muslims aged 19-34 years who have used paylater at least once. Sourced the data used in this study using primary data obtained from distributing questionnaires to 100 respondents. The result of this study indicates that life needs, peer attachment, and sharia financial literacy all significantly improve the decision to use PayLater. Lifestyle, however, has no bearing on the decision to use PayLater. Despite this, the separate factors influence PayLater usage decisions at the same time.